Exploring the multi-targeted mechanism of Saikosaponin A in prostate cancer treatment: a network pharmacology and molecular docking approach - Zhu, Genbao; Jiang, Zhiming; Zhu, Niuping; Wang, Donghui; Guo, Tianpeng; Meng, Yiqing; Zhu, Yi; Tan, Kemeng; Hu, Mengxue; Tang, Heng; Wang, Xuannian (Frontiers in Pharmacology, 2025)
BackgroundProstate cancer (PCa) is one of the prevalent malignant tumors among men. It can progress to castration-resistant prostate cancer (CRPC), which is significantly more challenging to treat. Saikosaponin A (SSA), a triterpenoid saponin extracted from the genus Bupleurum, exerts numerous pharmacological effects, including anti-inflammatory and anti-tumorigenic effects. However, the mechanism underlying the effects of SSA in prostate cancer treatment remains elusive.MethodsIn this study, a network pharmacology approach was applied to identify relevant targets from drug- and disease-related databases, and intersections were analyzed using Venny2.1 to construct a Protein-Protein interaction (PPI) interaction network. Next, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to elucidate associated biological functions and signaling pathways. Meanwhile, molecular docking between core targets and SSA was performed using Autodock software. Lastly, in vitro experiments were performed for validation.ResultsA least of four key targets, namely BCL2 apoptosis regulator (BCL2), estrogen receptor 1 (ESR1), hypoxia-inducible factor 1 subunit alpha (HIF1A), and signal transducer and activator of transcription 3 (STAT3) were identified in this study, and molecular docking analyses revealed that SSA stably binds to these targets. Moreover, the results of in vitro experiments revealed that SSA significantly inhibited the proliferative and migratory abilities of PC3 cells in a dose-dependent manner. Finally, SSA also induced G1-phase blockade and apoptosis in PC3 cells, further highlighting its potential role in prostate cancer treatment.ConclusionThe present study revealed that SSA exerts anti-tumorigenic effects in prostate cancer by targeting multiple pathways, laying a theoretical reference for its use as a therapeutic candidate for prostate cancer.